Host Intracellular Signaling Events and Pro-inflammatory Cytokine Production in African Trypanosomiasis - Kuriakose, Shiby M.; Singh, Rani; Uzonna, Jude E. (Frontiers in Immunology, 2016)
Pathogens such as bacteria, viruses and parasites possess specific molecules or proteins that are recognized by several host innate immune receptors leading to the activation of several intracellular signaling molecules and pathways. The magnitude and quality of these events significantly affect the outcome of infection. African trypanosomes, including Trypanosoma congolense, are capable of manipulating the host immune response, including the activity of macrophages, which are key immune cells that contribute to the immunopathogenesis of African trypanosomiasis. Although it is known that immune hyperactivation and excessive proinflammatory cytokine production are hallmarks of African trypanosomiasis, the mechanisms through which these events are triggered are poorly defined. However, it is known that macrophages may play a significant role in these processes because phagocytosis of trypanosomes by macrophages initiates intracellular signal transduction cascades that lead to release of proinflammatory cytokines and alteration in cell function. This review highlights recent progress in our understanding of the innate immune receptors, signaling pathways and transcription factors involved in T. congolense-induced pro-inflammatory cytokine production in by macrophages. It will reveal the existence of complex signaling events through which the parasite modulates the host immune response thus identifying novel targets that could aid in designing strategies to effectively control the disease.